AI for antibiotic discovery - de la Fuente, César (Henry Stewart Talks, 2025)
Antibiotic resistance, Intersection between machines and biology, AI in biology, Antibiotic design by computers, Drug development, Human proteome, Molecular de-extinction, AI for antibiotic discovery